2022
DOI: 10.1097/acm.0000000000004545
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Affairs Graduate Medical Education Expansion Addresses U.S. Physician Workforce Needs

Abstract: The United States has a well-trained, highly specialized physician workforce yet continues to have care gaps across the nation. Deficiencies in primary care and mental health specialties are most frequently cited, though critical shortages in multiple disciplines exist, particularly in rural areas. Sponsoring institutions of physician graduate medical education (GME) have created rural residency tracks with modest federal funding and minimal incentives, though efforts targeting shortages in these specialties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…However, contrary to the Act where priority was given to facilities in underserved areas with inadequate physician supply and high concentrations of Veterans, 22 our findings suggest that redistributing or expanding funded GME positions to areas with relatively higher social deprivation and lower-quality public schools may have little impact on addressing physician shortages, which was also shown in several studies. 22,44 Our findings indicate that expanding GME allocations in areas with good schools and relatively high socioeconomic status is likely to decrease time-to-fill in those areas. Stronger financial incentives such as offering greater recruitment and retention bonuses, raising salary caps, and expanding loan forgiveness programs may be needed to decrease time-to-fill in areas with relatively poor public schools or low socioeconomic status.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, contrary to the Act where priority was given to facilities in underserved areas with inadequate physician supply and high concentrations of Veterans, 22 our findings suggest that redistributing or expanding funded GME positions to areas with relatively higher social deprivation and lower-quality public schools may have little impact on addressing physician shortages, which was also shown in several studies. 22,44 Our findings indicate that expanding GME allocations in areas with good schools and relatively high socioeconomic status is likely to decrease time-to-fill in those areas. Stronger financial incentives such as offering greater recruitment and retention bonuses, raising salary caps, and expanding loan forgiveness programs may be needed to decrease time-to-fill in areas with relatively poor public schools or low socioeconomic status.…”
Section: Discussioncontrasting
confidence: 79%
“…The Veterans Access, Choice, and Accountability Act (the Choice Act) of 2014 provided funds to expand GME by 1500 positions to improve Veterans' access to medical care at the VA, with a priority for primary care, mental health, and any other specialties the secretary of VA determined appropriate. 22 There are multiple reasons to think this may work because physician residents made significant contributions to the production of clinical care net of their supervision in a cost-efficient way. 23 Also, the Trainee Satisfaction Survey conducted by the VA Office of Academic Affiliations (OAA) found that physician residents had a more positive opinion regarding a career at the VA after completing their rotations, and among them over half would consider a career at VA. 22 Teaching opportunities resulting from GME also improve the job satisfaction of VA clinicians, reduce burnout, and increase their retention at VA. 24 However, no previous project has examined the impact of the size of residency training programs on the recruiting success of the sponsoring institution, and whether the impact differs by the socioeconomic status and public school quality of the geographic area of the training program.…”
mentioning
confidence: 99%
“…These 5 tenets square solidly with the missions of the VA, and their themes are visited in 3 articles 16–18 appearing in this issue of our journal.…”
mentioning
confidence: 99%
“…The authors' findings resonate with the 5th mission of academic medicine, where everyone, including VA facility leaders, remains steadfast in their commitment to "repeated demonstrations of respect for persons, justice, inclusion, and integrity. " 15 In this issue, Klink et al 18 highlight the VA-academic medicine partnership through the Veterans Access, Choice and Accountability Act of 2014, which expanded GME capacity nationwide by adding 1,500 new positions in areas of need, including positions in primary care and mental health. The VA, as the second-largest funder of GME outside of the Centers for Medicare and Medicaid services, has been able to target both underserved locations and also the need for primary care and mental health in both the VA and the nation.…”
mentioning
confidence: 99%
See 1 more Smart Citation